Dimensions for Evaluating Cloud Resource Orchestration Frameworks. - Khoshkbarforoushha, Alireza; Wang, Meisong; Ranjan, Rajiv; Wang, Lizhe; Alem, Leila; Khan, Samee U.; Benatallah, Boualem (Computer (00189162), 2016)
Despite the proliferation of cloud resource orchestration frameworks (CROFs), DevOps managers and application developers still have no systematic tool for evaluating their features against desired criteria. The authors present generic technical dimensions for analyzing CROF capabilities and understanding prominent research to refine them.